Analisis Prinsip 5C untuk Meminimalisir Kredit Macet pada BUMDEsa Amanah Perspektif Syariah di Desa Bukit Gajah - Anisa Sulistiya; Muli Prima Aldi; Viras Alti Pidola; Tika Widiyan (Journal of Islamic Economic and Law (JIEL), 2025)
Bad debts are a serious problem in the management of BUMDEsa, so the application of the 5C principle is needed to assess the eligibility of prospective debtors and maintain the sustainability of financing. This study aims to analyze the application of the 5C principle in minimizing bad debts at BUMDEsa Amanah Desa Bukit Gajah as an effort to maintain the sustainability of financing. This type of research is qualitative. Data collection techniques, namely using observation, interviews, documentation. Data were obtained from the results of observations, interviews, and documentation. Based on the data collected starting from the results of observations, it can present the answer "yes" to the observation: 60%. Thus it can be concluded that analyzing the application of the 5C principle to minimize bad debts in village-owned enterprises(BUMDEsa) Amanah Bukit Gajah Village is categorized as Quite Optimal because it is 41% -60%. This result of a study that illustrates the importance of implementing the 5 C principle before providing credit to customers. To gain confidence and financing interests, financing must conduct a thorough assessment of character, ability, capital, collateral and economic conditions known as "5 C".